MOTIF KECURANGAN, ADANYA KESEMPATAN DAN MANIPULASI LABA - Shintya Dewi Adi Putri (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2015)
This research examines the relationship between fraud motives (leverage and dividends) and earnings manipulation; and the relationship between opportunities (quality audit and free cash flow) and earnings manipulation. This research used a sample of 24 companies listed on the Indonesia Stock Exchange in 2011-2013. The results of this research analysis is that there is a significant negative correlation between dividend payments and earningsmanipulation. This research also proved that free cash flow has a positive correlation with earnings manipulation.